CCAFS Gender Impact Pathway for Southeast Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Gender Impact Pathway for Southeast Asia. Prepared by CCAFS Southeast Asia representatives during the Gender Training and Strategizing Workshop held in Nairobi, Kenya in 2013. This document illustrates the suggested pathway for equality and impact in the region as it identifies current gender gaps, measures to fill those gaps, and the targeted outcomes for these activities as well as specific gender impacts for Southeast Asia.